THE RELATIONSHIP BETWEEN CHARACTERISTICS OF CONTRACEPTORS AND THE USE OF HORMONAL CONTRACEPTION WITH HYPERTENSION INCIDENT AT PALANG TUBAN COMMUNITY HEALTH CENTER - Munir, Miftahul; Sriutami, Ika (INTERNATIONAL JOURNAL OF MIDWIFERY RESEARCH, 2021)
Supporting factors for couples of childbearing age to choose contraceptives for each individual are different. The side effects are different for each method of contraception. One of the side effects is the incidence of hypertension. This study aims to determine the relationship between the characteristics of family planning acceptors and the use of hormonal family planning with the incidence of hypertension at the Palang Tuban Health Center.The population in this study were family planning acceptors at the Palang Health Center in August 2022 as many as 935 people. The sampling technique used is simple random sampling. The sample in this study were 280 family planning acceptors at the Palang Health Center in August 2022. The design of this research was analytical with a cross sectional approach. Data collection by looking at the medical records of the Palang Community Health Center family planning in August 2022. Using the chi square test (x2) with = 0.05 using the SPSS version 22 method program.The results showed that the characteristics of family planning acceptors at the Palang Health Center were between the ages of 20-35 years, parity > 2 children, working, junior high school education status, duration of use of hormonal contraception 1-5 years, using injection contraceptives, the presence of hypertension sufferers using hormonal contraception . . And the results of the chi square test data analysis (x2) showed age (62.147) = 0.980 parity (23.350) = 0.077, employment status (10.882) = 0.012, educational status (16.915) = 0.050, length of use of family planning ( 27,041) =0.000 types of contraception (153.657) = 0.000 use of hormonal contraception (151.213) = 0.000 where < 0.05.It can be concluded that there is a relationship between the characteristics of family planning acceptors from work status, duration of use of hormonal family planning, types of contraception and use of hormonal contraceptives with the incidence of hypertension at the Palang Tuban Health Center in 2022. Therefore, the introduction of side effects of hormonal family planning is very necessary.